Influence of fetal calf serum on the production of bovine embryos in vitro - Khanh Van Nguyen; Thi Kim Yen Pham; Thi Au Hoang; Quang Minh Luu; Doan Lan Pham (Vietnam Journal of Science, Technology and Engineering, 2023)
The aim of the present study was to evaluate the effect of foetal calf serum (FCS) on the production of bovine embryo in vitro. We conducted two experiments: (1) to evaluate the effect of FCS on the production of bovine embryo in vitro and (2) to evaluate the effect of duration of FCS supplementation on the production of bovine embryo in vitro. In experiment 1, we divided mature bovine oocytes after in vitrofertilization into four embryo culture media: CR1aa, CR1aa+FCS, SOFaa, and SOFaa+FCS. Embryos cultured in CR1aa and SOFaa media supplemented with FCS resulted in a higher cleavage and blastocyst formation rates than when cultured in CR1aa and SOFaa without FCS (74.22 and 82.96% vs. 71.6 and 70.62%; 4.11 and 22.31% vs. 16.98 and 34.51%; respectively, p<0.05). The percentage of hatching blastocysts was highest when embryos were cultured in SOFaa medium supplemented with FCS (10.54%; p<0.05). Embryos cultured in the medium with FCS had a higher the average number of cells/blastocyst than the medium without FCS. The SOFaa+FCS group had a higher average number of cells/embryos than the other groups (94.32; p<0.05). In experiment 2, we added FCS to bovine embryo culture in vitroat the following times: 0 h, 48 h, and 120 h after fertilization. The rate of oocyte cleavage, blastocyst formation, and hatching blastocyst rate of the 0-h group were higher than that of 48-h and 120-h groups (82.96 vs 70.5 and 70.24%; 34.51 vs 24.21 and 23.18%; 10.5 vs 6.12 and 4.13%; respectively, p<0.05). However, there was no difference in the average number of cells/blastocysts between the groups. In conclusion, the addition of FCS to embryo culture media improved the efficiency of bovine embryo production in vitroand in vitro bovine embryo quality. The appropriate time to add FCS to bovine embryo culture in vitrowas 0 h after fertilization.